Morphologic analysis, by means of scanning electron microscopy, of the effect of Er: YAG laser on root surfaces submitted to scaling and root planing (Pesquisa Odontológica Brasileira, 2002)
The purpose of this study was to morphologically evaluate, by means of scanning electron microscopy, the effects of Er:YAG laser on the treatment of root surfaces submitted to scaling and root planing with conventional periodontal instruments. Eighteen root surfaces (n = 18), which had been previously scaled and planed, were assigned to 3 groups (n = 6). The control Group (G1) received no further treatment; Group 2 (G2) was irradiated with Er:YAG laser (2.94 mum), with 47 mJ/10 Hz, in a focused mode with air/water spray during 15 s and with 0.57 J/cm² of fluency per pulse; Group 3 (G 3) was irradiated with Er:YAG laser (2.94 mum), with 83 mJ/10 Hz, in a focused mode with air/water spray during 15 s and with 1.03 J/cm² of fluency per pulse. We concluded that the parameters adopted for Group 3 removed the smear layer from the root surface, exposing the dentinal tubules. Although no fissures, cracks or carbonized areas were observed, an irregular surface was produced by Er:YAG laser irradiation. Thus, the biocompatibility of the irradiated root surface, within the periodontal healing process, must be assessed.